Annealing-induced precipitate formation behavior in MOVPE-grown GaAs1−xBix explored by atom probe tomography and HAADF-STEM. (4th May 2017) - Wood, Adam W; Chen, Weixin; Kim, Honghyuk; Guan, Yingxin; Forghani, K; Anand, A; Kuech, T F; Mawst, L J; Babcock, S E
Abstract: The effects of a 45 min anneal at 800 °C on the physical properties and microstructure of a five-period GaAs1− x Bi x /GaAs1− y Bi y superlattice with y  ≠  x were studied using room-temperature photoluminesence spectroscopy, high-resolution x-ray diffraction, high-angle annular-dark-field scanning transmission electron microscopy (HAADF-STEM), and atom probe tomography (APT). The anneal resulted in a substantial increase of the photoluminesence intensity over that observed in the as-deposited sample, indicating annihilation of non-radiative recombination centers and stability of the superlattice structure during the anneal. However, some precipitation of Bi from the GaAs1− x Bi x also occurred. The characteristics of phase separation that occurred within these precipitates were investigated in detail by APT and HAADF-STEM. They indicate that the precipitation reaction involves formation of embedded nano-scale liquid droplets that can accelerate local Bi dissolution from the GaAs1− x Bi x matrix by moving through it. Preservation of nanometer scale sharp Bi concentration gradients in the growth direction suggested that very little solid state diffusion of Bi occurred during the anneal. The observed gradient in precipitate number density with distance from the sample surface further supports hypotheses of an enabling role of Ga vacancies in the precipitation process.